Patient satisfaction from two studies of collaborative doctor – pharmacist prescribing in Australia. (23rd January 2015) - Hale, Andrew; Coombes, Ian; Stokes, Julie; Aitken, Stuart; Clark, Fiona; Nissen, Lisa
Abstract: Background: Pharmacist prescribing has been introduced in several countries and is a possible future role for pharmacy in Australia. Objective: To assess whether patient satisfaction with the pharmacist as a prescriber, and patient experiences in two settings of collaborative doctor‐pharmacist prescribing may be barriers to implementation of pharmacist prescribing. Design: Surveys containing closed questions, and Likert scale responses, were completed in both settings to investigate patient satisfaction after each consultation. A further survey investigating attitudes towards pharmacist prescribing, after multiple consultations, was completed in the sexual health clinic. Setting and Participants: A surgical pre‐admission clinic (PAC) in a tertiary hospital and an outpatient sexual health clinic at a university hospital. Two hundred patients scheduled for elective surgery, and 17 patients diagnosed with HIV infection, respectively, recruited to the pharmacist prescribing arm of two collaborative doctor‐pharmacist prescribing studies. Results: Consultation satisfaction response rates in PAC and the sexual health clinic were 182/200 (91%) and 29/34 (85%), respectively. In the sexual health clinic, the attitudes towards pharmacist prescribing survey response rate were 14/17 (82%). Consultation satisfaction was high in both studies, most patients (98% and 97%, respectively) agreed they were satisfied with the consultation. In the sexual health clinic, all patients (14/14) agreed that they trusted the pharmacist's ability to prescribe, care was as good as usual care, and they would recommend seeing a pharmacist prescriber to friends. Discussion and Conclusion: Most of the patients had a high satisfaction with pharmacist prescriber consultations, and a positive outlook on the collaborative model of care in the sexual health clinic.